(untitled) - Adler, Ronald B. (New York, 1992)
Contents: Communicating at work; Communication systems and cultures; Verbal and nonverbal messages; Problem solving, conflict management, and negotiation; Principles of interviewing...
Keywords: Business communication,Giao tiếp kinh doanh